2018
DOI: 10.1111/jpn.12914
|View full text |Cite
|
Sign up to set email alerts
|

Dietary concentrate level affects the feed sorting behaviour of lambs

Abstract: The objective of this study was to evaluate the effect of forage concentration on sorting, nutrient intake and feeding behaviour of growing lambs. Twelve weaned lambs were exposed, in a crossover design with 7-day periods, to each of two treatment diets: (i) lower-concentrate diet (LC; 40.0% concentrate) and (ii) a higher-concentrate diet (HC; 60.0% concentrate). Alfalfa hay was used as forage source. Sorting was determined by subjecting fresh feed and ort samples to particle separation and expressing the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sheep are known for their sorting behavior, being more intense than cattle and less intense than goats, which may result in an unbalanced intake of nutrients (i.e. not consuming enough or overconsumption), reduction of the nutritive value of the ration, alteration of rumen fermentation, unexpected performance, and increased risks of rumen disorders ( Miller-Cushon and DeVries, 2017 ; Sari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep are known for their sorting behavior, being more intense than cattle and less intense than goats, which may result in an unbalanced intake of nutrients (i.e. not consuming enough or overconsumption), reduction of the nutritive value of the ration, alteration of rumen fermentation, unexpected performance, and increased risks of rumen disorders ( Miller-Cushon and DeVries, 2017 ; Sari et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sorting index of the material remaining in the bottom pan of BGH diets, which was calculated as the actual DMI of each fraction of the PSPS divided by the predicted DMI of that fraction ( Leonardi and Armentano, 2003 ), was 126%; this indicates that the lambs sorted for it. Indeed, feedlot lambs sort most against the longest particles and fine particles ( Sari et al, 2018 ). Therefore, the capacity of animals that sorted for the concentrate when fed BGH influenced DMI so that they could consume less ration and maintained similar growth performance compared to cob diets.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavior in lambs has been previously reported. For example, Sari et al (2018) reported increased FI/V and FR with increasing concentrate level in the diet, which may have been due to improved palatability and higher rates of ruminal degradation and passage of concentrates compared to forage. Moreover, the ruminal microbiota is responsible for ruminal degradation of food, which might play a role in the observed differences in eating behavior.…”
Section: Discussionmentioning
confidence: 99%